Sphincter-preserving surgery after preoperative radiochemotherapy for T3 low rectal cancers - BAI, XUE (D.A. Spandidos, 2012)
The aim of this study was to evaluate the feasibility and the effectiveness of preoperative radiochemotherapy followed by total mesorectal excision (TME) and sphincter-preserving procedures for T3 low rectal cancer. Patients with rectal cancer and T3 tumors located within 1–6 cm of the dentate line received preoperative radiochemotherapy. Concurrent 5-fluorouracil-based radiochemotherapy was used. Radical resection with TME and sphincter-preserving procedures were performed during the six to eight weeks following radiotherapy. Survival was analyzed using the Kaplan-Meier method. The anal function was evaluated using the Wexner score. The clinical response rate was 83.5%, overall downstaging of T classification was 75.3% and pathological complete response was 15.3%. The anastomotic fistula rate was 4.7%. A median follow-up of 30 months showed the local recurrence rate to be 4.7% and the distant metastasis rate to be 5.9%. The three-year overall survival rate was 87%. The degree of anal incontinence as measured using the Wexner score decreased over time, and the anal sphincter function in the majority of patients gradually improved. Preoperative radiochemotherapy was found to improve tumor downstaging, reduces local recurrence, increase the sphincter preservation rate, and is therefore of benefit to patients with T3 low rectal cancer.